Clinical impact of variants in non-coding regions of SHOX - Current knowledge - Spurna, Zuzana; Capkova, Pavlina; Srovnal, Josef; Duchoslavova, Jana; Punova, Lucia; Aleksijevic, Darina; Vrtel, Radek (Gene, 2022)
The short stature homeobox-containing (SHOX) is the most frequently analysed gene in patients classified as short stature patients (ISS) or diagnosed with Leri-Weill dyschondrosteosis (LWD), Langer mesomelic dysplasia (LMD), or Madelung deformity (MD). However, clinical testing of this gene focuses primarily on single nucleotide variants (SNV) in its coding sequences and copy number variants (CNV) overlapping SHOX gene. This review summarizes the clinical impact of variants in noncoding regions of SHOX. RECENT FINDINGS: CNV extending exclusively into the regulatory elements (i.e., not interrupting the coding sequence) are found more frequently in downstream regulatory elements of SHOX. Further, duplications are more frequent than deletions. Interestingly, downstream duplications are more common than deletions in patients with ISS or LWD but no such differences exist for upstream CNV. Moreover, the presence of specific CNVs in the patient population suggests the involvement of additional unknown factors. Some of its intronic variants, notably NM_000451.3(SHOX):c.-9delG and c.-65C>A in the 5'UTR, have unclear clinical roles. However, these intronic SNV may increase the probability that other CNV will arise de novo in the SHOX gene based on homologous recombination or incorrect splicing of mRNA. SUMMARY: This review highlights the clinical impact of noncoding changes in the SHOX gene and the need to apply new technologies and genotype-phenotype correlation in their analysis.
Keywords: CNV; DNA, Intergenic; Gene Expression Regulation; Non-coding region; LWD; genetická variace; fenotyp; ISS; haploinsuficience; Genetic Variation; regulace genové exprese; SHOX; Phenotype; intergenová DNA; Humans; Short Stature Homeobox Protein; Haploinsufficiency; protein SHOX; SNV; lidé